2023
DOI: 10.1261/rna.079699.123
|View full text |Cite
|
Sign up to set email alerts
|

Localization of unlabeled bepirovirsen antisense oligonucleotide in murine tissues using in situ hybridization and CARS imaging

Abstract: Current methods for detecting unlabelled ASOs rely on immunohistochemistry and/or conjugated molecules, which lack sufficient sensitivity, specificity and resolution to fully investigate their bio-distribution. Our aim was to demonstrate the qualitative and quantitative distribution of unlabelled bepirovirsen, a clinical stage ASO, in livers and kidneys of dosed mice using novel staining and imaging technologies at sub-cellular resolution. ASOs were detected in FFPE and frozen tissues using an automated chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…In renal tubules, Sperati et al identified the spectroscopic signature of intratubular triamterene crystals, a diuretic that is linked to kidney stone formation . Spencer-Dene et al combined CARS imaging with an miRNAscope in situ hybridization (ISH) assay to monitor the distribution of bepirovirsen in murine kidney and liver tissues . While a few studies have explored direct imaging of drugs in internal organ tissue, the overwhelming majority has focused on the skin.…”
Section: Imaging Drug Molecule Distribution and Delivery In Cells And...mentioning
confidence: 99%
See 1 more Smart Citation
“…In renal tubules, Sperati et al identified the spectroscopic signature of intratubular triamterene crystals, a diuretic that is linked to kidney stone formation . Spencer-Dene et al combined CARS imaging with an miRNAscope in situ hybridization (ISH) assay to monitor the distribution of bepirovirsen in murine kidney and liver tissues . While a few studies have explored direct imaging of drugs in internal organ tissue, the overwhelming majority has focused on the skin.…”
Section: Imaging Drug Molecule Distribution and Delivery In Cells And...mentioning
confidence: 99%
“…95 Spencer-Dene et al combined CARS imaging with an miRNAscope in situ hybridization (ISH) assay to monitor the distribution of bepirovirsen in murine kidney and liver tissues. 96 While a few studies have explored direct imaging of drugs in internal organ tissue, the overwhelming majority has focused on the skin. This is likely due to the accessibility and integrity of skin tissue samples and their ease of preparation for imaging.…”
Section: Delivery In Cells and Tissuesmentioning
confidence: 99%